2022
DOI: 10.3389/fnagi.2022.932541
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Tau Aggregates Between Clearance and Transmission

Abstract: Neuronal accumulation of mis-folded tau is the pathological hallmark of multiple neurodegenerative disorders, including Alzheimer’s disease. Distinct from amyloid plaques, which appear simultaneously throughout the brain, tau pathology develops first in a specific brain region and then propagates to neuroanatomically connected brain regions, exacerbating the disease. Due to the implication in disease progression, prevention of tau transmission is recognized as an important therapeutic strategy that can halt di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 160 publications
0
3
0
Order By: Relevance
“…In the present study, we investigated the roles of CR3 and CR4 in the clearance of extracellular tau by microglia. Because mounting evidence has shown that extracellular tau exist in various forms, such as monomers and aggregates, mostly as vesicle-free forms [17][18][19][20][21][22][23][24][25][26][27][28][29], we focused on the clearance of vesicle-free tau monomers and fibrils through these two complement receptors by microglial cells. Here, we provide evidence that CR4 but not CR3 is a phagocytic receptor specific for tau fibrils that mediates the clearance of extracellular tau fibrils by BV2 microglial cells as well as primary microglia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we investigated the roles of CR3 and CR4 in the clearance of extracellular tau by microglia. Because mounting evidence has shown that extracellular tau exist in various forms, such as monomers and aggregates, mostly as vesicle-free forms [17][18][19][20][21][22][23][24][25][26][27][28][29], we focused on the clearance of vesicle-free tau monomers and fibrils through these two complement receptors by microglial cells. Here, we provide evidence that CR4 but not CR3 is a phagocytic receptor specific for tau fibrils that mediates the clearance of extracellular tau fibrils by BV2 microglial cells as well as primary microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise molecular mechanisms underlying the propagation of tau pathology remain elusive, several pathways have been suggested for the secretion of tau, such as vesicle-mediated pathways through exosomes [16], ectosomes [17] and vesicle-free direct translocation across the plasma membrane [18,19]. Although the amount and types of extracellular tau vary depending on the disease status, different forms of tau, such as monomers and aggregates, exist in the extracellular space mostly in vesicle-free forms [17][18][19][20][21][22][23][24][25][26][27][28][29]. Besides mediating cell-to-cell transmission, extracellular tau is toxic to neurons by inducing neuritic degeneration, perturbing axonal transport and impairing memory [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation